Dissolution behaviour of lime in vanadium extraction slag. (April 2015) - Tang, R.; Wang, Y.; Zhang, C. J.; Xie, B.; Diao, J.
<x content-type="archive" xml:space="preserve">Abstract</x> During the converter vanadium extraction process, phosphorus cannot be removed from hot metal due to the absence of CaO in the slag. In order to lower the phosphorus content and produce CaO-containing vanadium slag, which could be directly used in a subsequent roasting process, lime dissolution in FeOx–SiO2–V2O3–TiO2 slag was investigated using a rotating disk/cylinder technique. Kinetics of dissolution were correlated with the Levich–Cochran equation for a rotating disc and used to determine the effective diffusivity of lime. The results show that dissolution rates were several times greater than previous studies in the BF/BOF slag system and were strongly dependent on the rotation speed, indicating mass transfer to be the rate-limiting step. The diffusivity of CaO in slag was calculated from the dissolution rate and solubility data, and was inversely proportional to the viscosity of the slag. The effects of temperature and revolution speed on the dissolution of lime were analysed and discussed.